Stairlike Aurivillius Phases in the Pseudobinary Bi5Nb3O15-ABi2Nb2O9 (A = Ba and Sr) System: A Comprehensive Analysis Using Superspace Group Formalism - Steciuk, Gwladys; Barrier, Nicolas; Pautrat, Alain; Boullay, Philippe (Inorganic chemistry, 2018)
We report the possibility of extending the so-called stairlike Aurivilius phases in the pseudobinary Bi5Nb3O15-ABi2Nb2O9 (A = Ba and Sr) over a wide range of compositions. These phases are characterized by a discontinuous stacking of [Bi2O2] slabs and perovskite blocks, leading to long-period intergrowths stabilized as a single phase. When analyses from precession electron diffraction tomography and X-ray and neutron powder diffraction are combined, the monoclinic incommensurately modulated structure with q = αa* + γc* previously proposed for the ABi7Nb5O24 composition could be generalized to the Bi5Nb3O15-ABi2Nb2O9 (A = Ba and Sr) compounds. Considering the compositions expressed as (A,Bi)1- xNb xO3-3 x, the stacking sequence associated with compositions ranging from x = 2/5 to 3/8 is governed by the component γ of the modulation vector and can be predicted following a Farey tree hierarchy independently to the A cation. The length of the steps, characteristic of the stairlike nature, is controlled by the α component and depends on the substitution ratio A/Bi and the nature of A (A = Ba and Sr). This study highlights the compositional flexibility of stairlike Aurivillius phases.